Human immunodeficiency virus in institutionalized elderly people - Gorzoni, Milton Luiz; Pires, Sueli Luciano; Faria, Lilian de Fátima Costa; Aguado, Márcia Regina Valadares; Santana, Miriam Carmen (São Paulo Medical Journal, 2016)
CONTEXT AND OBJECTIVE: A search in the SciELO and PubMed databases showed few studies on human immunodeficiency virus (HIV) positive individuals in long-term care institutions (LTCIs), thus prompting the present study. The aim of this study was to ascertain whether there were any HIV-positive individuals in LTCIs for the elderly. DESIGN AND SETTING: Cross-sectional study in which the Hospital Infection Control Committee (HICC) of a 405-bed LTCI was consulted. METHODS: The medical records of 405 individuals interned in the LTCI who had been tested for HIV infection were requested for analysis of the following variables: [1] age and gender; [2] length of stay at LTCI (months); [3] causes and diagnoses on admission to LTCI according to International Classification of Diseases, 10th edition; [4] date of HIV diagnosis; [5] seropositivity for syphilis and hepatitis B and C viruses; [6] medications used at last prescription in medical file; and [7] mean CD4 lymphocyte count based on: total lymphocyte count/6 and total lymphocyte count x 0.8 x 0.2 or 0.3. RESULTS: Four men were HIV-positive, with mean age 71.2 ± 8.6 years, LTCI stay 74.2 ± 38.1 months and length of HIV diagnosis 24.5 ± 17 months (confirmed by HICC standard screening). Three had stroke sequelae; one, dementia syndrome; two, seropositivity for syphilis; two, hepatitis B and one, hepatitis C. The main drugs used were lamivudine, zidovudine, lopinavir, ritonavir, levothyroxine, omeprazole, ranitidine, lactulose and risperidone. The estimated CD4 count was 341 ± 237/mm3 . CONCLUSIONS: HIV-positive individuals are present in LTCIs, diagnosable through serological screening and treatable with antiretroviral drugs.